The Relationship Of Knowledge About Reproductive Health To Adolescent Sex Behavior In State Vocational School I Sibolga In 2020 - Tinawati Nainggolan (Science Midwifery, 2021)
Teenagers' great curiosity, the development of information technology, the lack of communication in the family, and the increasingly indifferent society make this behavior more widespread. The purpose of this study was to determine the relationship between the level of knowledge of reproductive health and the free sex behavior of office-class adolescents at SMK Negeri 1 Sibolga. This type of research uses descriptive quantitative with cross sectional design. Based on the results of the study, the Chi-square test results obtained p value = 0.000 < from 0.05 (0.000 <0.05). So that Ha is accepted and Ho is rejected, which means that there is a relationship between the level of knowledge of reproductive health and free sex behavior in adolescents at SMK Negeri I Sibolga City in 2020. The better the knowledge about sexuality, the better the sexual behavior, reinforced by Green's theory that knowledge is a predisposing factor. determine a person's behavior. The school is expected to pay attention to the reproductive health education curriculum for students in order to protect students from inappropriate knowledge that comes from irresponsible sources. It is hoped that students can avoid deviant sexual behavior, such as watching pornographic videos and avoiding watching YouTube and reading books that related to sexual behavior so that things do not happen that are disappointing for the family, school and community.